2017
DOI: 10.1097/md.0000000000006660
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of treatment-naive patients with hepatitis B virus infection

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…An estimated figure has shown that less than 5% of rural patients are able to afford 1 year of treatment as opposed to 40% of patients in more developed regions [29]. In addition to issues concerning accessibility and costs of treatment, Chinese patients in rural regions also have poor health awareness; many infected-individuals are unaware of their HBV infection until symptoms appear [31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…An estimated figure has shown that less than 5% of rural patients are able to afford 1 year of treatment as opposed to 40% of patients in more developed regions [29]. In addition to issues concerning accessibility and costs of treatment, Chinese patients in rural regions also have poor health awareness; many infected-individuals are unaware of their HBV infection until symptoms appear [31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…Second, a diminished estimated glomerular filtration rate, hypophosphatemia, hyperphosphaturia, and Fanconi syndrome have been reported in patients using TDF (11)(12)(13). Lastly, more than 50% of patients infected with CHB are between the ages of 40 and 59 years putting them at a high risk of bone and kidney injury (14).…”
Section: Introductionmentioning
confidence: 99%